How do mental health practitioners operationalise cultural competency in everyday practice? A qualitative analysis - Tooba Noor Mollah; Josefine Antoniades; Fathima Ijaza Lafeer; Bianca Brijnath (BMC, 2018)
Abstract Background Despite continued policy and research emphasis to deliver culturally competent mental healthcare, there is: (1) limited evidence about what frontline practitioners consider to be culturally competent care and; (2) what helps or hinders them in delivering such care in their everyday practice. The aims of this article are to address these gaps. Methods Qualitative in-depth interviews were conducted with 20 mental health practitioners working with immigrant patients to explore their understandings and experiences of culturally competent care. Interviews were conducted between September 2015 and February 2016 in the state of Victoria, Australia. Data were thematically analysed. Results There were common understandings of cultural competence but its operationalisation differed by profession, health setting, locality, and years of experience; urban psychiatrists were more functional in their approach and authoritarian in their communication with patients compared to allied health staff in non-specialist mental health settings, in rural areas, with less years of experience. Different methods of operationalising cultural competence translated into complex ways of building cultural concordance with patients, also influenced by health practitioners' own cultural background and cultural exposures. Limited access to interpreters and organisational apathy remain barriers to promoting cultural competency whereas organisational support, personal motivation, and professional resilience remain critical facilitators to sustaining cultural competency in everyday practice. Conclusion While there is need for widespread cultural competence teaching to all mental health professionals, this training must be specific to different professional needs, health settings, and localities of practice (rural or urban). Experiential teaching at tertiary level or professional development programs may provide an avenue to improve the status quo but a 'one-size-fits-all' model is unlikely to work.